Workability assessment of structural steels of power plant units in hydrogen environments - Balitskii, A.I.; Panasyuk, V.V. (Проблемы прочности, 2009)
For estimation of hydrogen influence on the workability of high-stressed parts of power plant unit equipment it is necessary to use the crack growth resistance parameters. The new 18Mn-18Cr steel has higher resistance to hydrogen embrittlement and longer residual life time in hydrogen, than the traditional 8Mn-8Ni-4Cr steel.